The role of decentralized generation and storage technologies in future energy systems planning for a rural agglomeration in Switzerland. (September 2016) - Yazdanie, Mashael; Densing, Martin; Wokaun, Alexander
Abstract: This study presents a framework to quantitatively evaluate decentralized generation and storage technology (DGST) performance and policy impacts in a rural setting. The role of DGSTs in the future energy systems planning of a rural agglomeration in Switzerland is examined using a cost optimization modeling approach. Heat and electricity demand for major sectors are considered. Scenarios introduce DGSTs in a stepwise manner to measure incremental impacts on future capacity planning compared to a baseline scenario. Sub-scenarios also examine the impacts of carbon mitigation policies, and a sensitivity analysis is carried out for key energy carriers and conversion technologies. DGSTs enable a significant reduction in electricity grid usage for the community considered. Small hydro with a storage reservoir and photovoltaics enable the community to become largely self-sufficient with over 80% reductions in grid imports by 2050 compared to the baseline scenario. Storage enables maximum usage of the available hydro potential which also leads to network upgrade deferrals and a significant increase in photovoltaic installations. Investment decisions in small hydro are robust against cost variations, while heating technology investment decisions are sensitive to oil and grid electricity prices. Carbon pricing policies are found to be effective in mitigating local fossil fuel emissions. Highlights: Rural case study on decentralized generation and storage technology (DGST) benefits. Cost optimization model and scenarios developed to assess DGSTs until 2050. Small hydro and photovoltaics (PV) increase self-sufficiency of community. Storage enables full hydro potential usage and increased PV penetration. Carbon price policies effective in mitigating local fossil fuel emissions.